Name_____________________________

MULTIPLYING BINOMIALS

Directions:  Find the product of each pair of binomials below.  Combine all like terms and write the product in simplest form on the line provided next to each expression.

Example:  (2x + 5) (4x + 1) =   =

1)         (2x + 2) (4x + 3)  =                                                                              _________________

2)         (3x + 6) (2x + 7)  =                                                                              _________________

3)         (9x + 8) (3x + 2)  =                                                                              _________________

4)         (4x + 1) (5x + 9)  =                                                                              _________________

5)         (4x + 5) (4x + 5)  =                                                                              _________________

6)         (8x + 2) (2x + 7)  =                                                                              _________________

7)         (2x + 4) (6x + 3)  =                                                                              _________________

8)         (9x + 1) (x + 1)  =                                                                                _________________

9)         (3x + 3) (x + 7)  =                                                                                _________________

10)       (6x + 8) (7x + 9)  =                                                                              _________________

Name_____________________________

MULTIPLYING BINOMIALS

Directions:  Find the product of each pair of binomials below.  Combine all like terms and write the product in simplest form on the line provided next to each expression.

Example:  (2x + 5) (4x + 1) =   =

1)         (2x + 2) (4x + 3)  =

2)         (3x + 6) (2x + 7)  =

3)         (9x + 8) (3x + 2)  =

4)         (4x + 1) (5x + 9)  =

5)         (4x + 5) (4x + 5)  =

6)         (8x + 2) (2x + 7)  =

7)         (2x + 4) (6x + 3)  =

8)         (9x + 1) (x + 1)  =

9)         (3x + 3) (x + 7)  =

10)       (6x + 8) (7x + 9)  =